A Retrospective Study Of Hematological Parameters In Male And Female Hostel Residents Of (Ripans) Regional Institute Of Paramedical And Nursing Sciences, Aizawl, Mizoram - Khieya, Viswedeno; R. Elizabeth, R. Elizabeth; Das, Anamika; Sinha, Susmita; Lalremruati, Catherine; Jayarajan D, Jayarajan D (Journal of Neonatal Surgery, 2025)
Haematological parameters are assessed through laboratory tests and are essential for diagnosing and monitoring diseases such as anaemia, infections, clotting disorders, and haematological malignancies. A pilot observational study was performed on 140 hostel students of both boys and girls in at Regional Institute of Paramedical and Nursing Sciences, Aizawl, Mizoram, India where 64.3% (n = 90) of students among the total expressed haematological abnormalities and Hyper-segmented neutrophils during the study. The results recorded the significant level of abnormal in all haematological parameters compared with healthy controls and the significance was given as student’s test (p<0.001)